Analysis of Revenue Inequality and Development of Leading Economic Sectors of District and City in Banten Province, Indonesia - Bima Mulia; Mohamad Arief Setiawan; kalfin Kalfin (Research Collaboration Community (RCC), 2021)
The imbalance of inter-regional economic development is a common phenomenon that occurs in the process of economic development of a region. This interregional inequality was originally caused by differences in natural resource content and differences in demographic conditions in each region. As a result of these differences, the ability of an area to increase economic growth and encourage the development process also becomes different. Therefore, it is not surprising that in every region there is usually a relatively developed region and a relatively underdeveloped region. This study aims to analyze how big the level of income inequality that occurs between regencies/cities in Banten Province. Identifying the base sector in each district/city in Banten Province, and predicting the base sector in the future in each Regency/City of Banten Province. Data used in this study is secondary data in the form of time series data to see Developments and changes that occur over a period of time. Data analysis used in this research is Location Quotient (LQ), Dynamic Location Quotient (DLQ), Williamson and Thiel Index. The results of this study are inequality that occurred in Banten is measured by using Williamson Index included in the category of Medium Inequality. On the measurement of Thiel Entropy Index, inequality in Lebak Regency is the lowest and Kota Cilegon has the highest imbalance in Banten Province.